Resistant hypertension - Iza Stoll, Agustín (2013)
Resistant hypertension is defined as blood pressure that remains above target in spite of using three optimally dosed antihypertensive drugs of different classes, and one of the three drugs should be a diuretic. Patients whose blood pressure is controlled but requiring 4 or more drugs are also considered as resistant to treatment. Analyses of large scale trials of antihypertensive drugs point to a 10-20% prevalence of resistant hypertension in the general hypertensive population. Patients with resistant hypertension are almost 50% more likely to experience an adverse cardiovascular event compared with those with controlled blood pressure using three or less antihypertensive agents. Studies indicate that 5-10% of patients with resistant hypertension have an underlying secondary cause for their elevated blood pressure - a prevalence significantly greater compared to that of the general hypertensive population. The best available evidence supports the use of low dose spironolactone as the preferred fourth antihypertensive drug if the patient's blood potassium level is low. With higher blood potassium levels, intensification of thiazide-like diuretic therapy should be considered. Renal sympathetic denervation therapy, as a device based intervention, could potentially stimulate a paradigm shift in the management of resistant hypertension.